1986
DOI: 10.2307/2061410
|View full text |Cite
|
Sign up to set email alerts
|

Mortality by nativity

Abstract: This note reports the reversal of the mortality-nativity relationship in the United States. In the first half of the twentieth century, mortality among foreign-born Americans was greater than among (white) native Americans. Data for 1980 show that now mortality among the foreign-born is markedly lower than among native Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 2 publications
2
17
0
3
Order By: Relevance
“…Nevertheless, this was not possible, even though it would have resolved any numerator effect, a longer time lapse might possibly have added unwanted confounding factors into the analysis. However, the findings encountered are consistent with current literature, complementing the studies by Herring et al (2008), Franzini et al (2000), Kestenbaum (1986), Sharma et al (1990), Sorlie et al (1993), Uitenbroek & Verhoeff, (2002), and Chamizo-Garcia (2013).…”
Section: Bonilla Y Chavarríasupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, this was not possible, even though it would have resolved any numerator effect, a longer time lapse might possibly have added unwanted confounding factors into the analysis. However, the findings encountered are consistent with current literature, complementing the studies by Herring et al (2008), Franzini et al (2000), Kestenbaum (1986), Sharma et al (1990), Sorlie et al (1993), Uitenbroek & Verhoeff, (2002), and Chamizo-Garcia (2013).…”
Section: Bonilla Y Chavarríasupporting
confidence: 90%
“…In industrialized countries, research on mortality differentials between immigrants and local populations has focused on the "South to North" migration context. In general, these studies have found a mortality rate benefit in favor of immigrants versus the local population, in spite of the fact that the former have a lower socioeconomic status (Kestenbaum, 1986, Sharma et al, 1990Sorlie, Backlund, Johnson & Rogot, 1993;Uitenbroek & Verhoeff, 2002). In the context of migration to the United States, there is a so-called Hispanic paradox, where paradoxically Hispanic migrants in that country have health levels that are substantially better than the mean for the local population, in spite of the migrants' disadvantaged socio-economic indicators (Franzini, Ribble & Keddie, et 2000).…”
mentioning
confidence: 99%
“…5 The immigrant population in the 1986 study had 18% lower overall mortality than the USborn population, compared with 17% in this study. Nativity differences in relative risks of death from cancer, heart disease, and other cardiovascular diseases were also similar in the 2 studies.…”
Section: Discussionmentioning
confidence: 47%
“…[4][5][6][7] Analysis of immigrant mortality patterns has focused mostly on perinatal and infant mortality, where immigrants from various ethnic backgrounds are generally shown to have more favorable birth outcomes than their US-born counterparts. [8][9][10][11] In terms of morbidity and other nonmortality measures of health status, such as self-assessed health; number of restricted-activity days, bed disability days, work-loss days, and physician visits; and hospitalization rates, immigrants generally do better than the comparable US-born population.…”
mentioning
confidence: 99%
“…Même à 65 ans, les écarts demeurent importants : 4 ans de plus pour les immigrants non européens. On peut toutefois se demander ce que signifie une espérance de vie à la naissance pour des personnes nées à l'extérieur du Canada, la mortalité aux jeunes âges Notes : La répartition de la population de la Suède (1950Suède ( -1989 de pays, 1955-1959 à 1985-1989 1955-1960-1965-1970-1975-1980-1985-1959 1964 1969 1974 1979 1984 1989 1955-1960-1965-1970-1975-1980-1985-1959 1964 1969 1974 1979 1984 1989 Tiré de Bourbeau et Desjardins (2000); Suède : générations 1886-1890; USA (blancs) : période 1991-1992Canada : période 1991Canada : période -1994France : période 1991France : période -1995Japon : période 1991Japon : période -1995 FIGURE 2 -Quotients de mortalité des centenaires selon l 'âge, sexe féminin, Québec (natifs, générations 1885'âge, sexe féminin, Québec (natifs, générations -1889'âge, sexe féminin, Québec (natifs, générations ) et divers pays (période 1991'âge, sexe féminin, Québec (natifs, générations -1995 (Brahimi, 1980), en Australie (Young, 1986(Young, , 1987(Young, et 1991, en Angleterre et Pays de Galles (Marmot et al, 1983;Wild et McKeigue, 1997) et aux États-Unis (Jacobson, 1963;Kestenbaum, 1986) Pour l'Australie, les études de Young (1986de Young ( , 1991 Si on a pu montrer que la mortalité globale des immigrants est généralement plus faible que celle des natifs d'un pays, on a peu étudié les différences de mortalité aux grands âges. Étant donné le profil particulier de la mortalité canadienne à ces âges, il convient de l'examiner de plus près.…”
unclassified